Dietary Behavior of Drosophila melanogaster Fed with Genetically-Modified Corn or Roundup® - Raquel Elias; Becky Talyn; Erik Melchiorre (MDPI AG, 2021)
With the rise in concern about GMOs and pesticides on human health, we have utilized Drosophila melanogaster as a model organism for understanding the effects of Roundup-Ready® GMO diets on health. We recorded dietary behavior during and after exposure to a medium containing GMO or non-GMO corn, Roundup® in organic corn medium, and sucrose with or without one of the two Roundup® formulations. No differences in behavior were observed when Drosophila were exposed to a medium containing Roundup-Ready® GMO or non-GMO corn. Drosophila can detect and refrain from eating sucrose containing one Roundup® formulation, Ready-to-Use, which contains pelargonic acid in addition to glyphosate as an active ingredient. Drosophila exhibited dose-dependent increased consumption of sucrose alone after exposure to a medium containing either Roundup® formulation. This may indicate that flies eating a medium with Roundup® eat less and were thus hungrier when then given sucrose solution; that a medium with Roundup® is more difficult to digest; or that a medium with Roundup® is less nutritious, as would be the case if nutritionally important microbes grew on control medium, but not one containing Roundup®.